Maternal and fetal outcome in pregnant women after nutritional health education program: An interventional study at Zagazig university hospitals - Soliman, Alzahraa Mohammad; Hassan, Alsayed; Henary , Howaida; Abdelsalam, Amira; Abdo , Mostafa (Progress in Nutrition, 2019)
Background: Nutrition during pregnancy is an important element for the pregnant women and their fetus, they must take enough calories and nutrients to provide the essential requirements for both themselves and their fetus and to prevent complications of abnormal weight gain in pregnancy. Objectives: To determine the effect of the nutritional health education on changing knowledge, attitude and practice towards healthy pregnancy, obtaining optimal weight and its effect on obstetric outcome. Subjects and Methods; An interventional study (pre-posttest) was conducted in Zagazig university antenatal care clinic and included 135 pregnant female. Methods: Data collection was done through a semi-structured questionnaire about females’ socio-demographic characteristics, obstetric, family and clinical history. Health education sessions were applied on the pregnant females and their knowledge, attitude and practice about healthy nutrition were assessed before and after the intervention. Ultrasound was performed, obstetric outcomes were detected. Results: This study was conducted on 135 pregnant female. After the nutritional education program, the proportion of adequate knowledge, attitude and practice was increased from (28.2% to 77.3%-8.2% to 75.5% and 32.7% to 77.3%) respectively (p-value